1969
DOI: 10.1021/i160029a007
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport of Binary Electrolytes in Membranes. Concentration Dependence for Sodium Chloride Transport in Cellulose Acetate

Abstract: Equations describing the transport of water and a binary salt through semipermeable membranes are presented. Methods of experimentally determining the resulting six independent transport parameters have been tested. Measurements of these parameters on Loeb-type membranes are presented for curing temperatures of 75°, 84°, and 95°C. If the membrane concentration is characterized by the geometric mean activities of adjacent solutions, the osmosis parameters as defined are concentration-independent up to 0.1 M. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…To describe the transport phenomenon of water and a single solute in a binary electrolyte system through semi-permeable membranes, Bennion and Rhee (1969) have integrated a set of thermodynamic water and solute flux equations by assuming the water flux is not influenced by coupling the salt flux during reverse osmosis, while the salt flux shows coupling to water flow. The proposed water flux equation as follows:…”
Section: The Bennion and Rhee Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To describe the transport phenomenon of water and a single solute in a binary electrolyte system through semi-permeable membranes, Bennion and Rhee (1969) have integrated a set of thermodynamic water and solute flux equations by assuming the water flux is not influenced by coupling the salt flux during reverse osmosis, while the salt flux shows coupling to water flow. The proposed water flux equation as follows:…”
Section: The Bennion and Rhee Modelmentioning
confidence: 99%
“…They argued that there is no significant solute-solute interaction in multi-component systems. In fact, they based their thinking on the model of Bennion and Rhee (1969), which describes the fluxes of water and solute for a single solute system and modified this model in order to make it compatible for a system with two ionic and non-ionic solutes, which is given by:…”
Section: The Clifton and Fowler Modelmentioning
confidence: 99%
“…Michaels et al (1964) performed reverse osmosis experiments on various water-salt systems. They varied the applied pressure and found that salt flux, Ne, had the following pres- This is merely a special case of the more general equations proposed by Sherwood et al (1967), Bennion (1966), and Bennion and Rhee (1969).…”
mentioning
confidence: 89%
“…In a frictional membrane model, the driving force on a species is related to a linear sum of frictional interactions between the various species and the membrane. Spiegler (1958), Kedem and Katchalsky (1961), Bennion (1966), Wills and Lightfoot (1966), and Bennion and Rhee (1969) have provided extensive treatments of frictional membrane models. Spiegler (1958) and Wills and Lightfoot (1966) both proposed different methods applicable to ion exchange membranes where one ionic species is absent from the membrane.…”
mentioning
confidence: 99%
“…For the sulfuric-acid/Nafion-ll7' system, our experimental results (6) indicate that dilutesolution equations are suitable. For membrane-electrolyte systems in which dilute-solution theories cannot be apphed, transport models based on the principles of irreversible thermodynamics have proven useful (29)(30)(31)(32)(33)(34)(35), although a large number of unknown coefficients must be evaluated if no restrictive approximations are introduced. Equation [1] can be derived for transport in a homogeneous medium by making use of Eyring's absolute-reactionrate theory for diffusion processes (36)(37)(38).…”
Section: Mathematical Modelmentioning
confidence: 99%